Extraction and Characterization of the Water Soluble Polysaccharides from Coffee Pulp of Arabica (Coffea arabica) and Robusta (Coffea canephora) Variety - Diniyah, Nurud; Sulistia, Demi; Subagio, Achmad; nafi', Ahmad (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
The research was aimed to extract and characterize water soluble polysaccharides (WSP) from coffee pulp of arabica and robusta variety. The effect of extraction temperature i.e 80 and 90 °C on properties of WSP was investigated. The results showed that WSP produced from coffea robusta in combination with 90 °C of extraction temperature was the best treatment. It yielded WSP of 10.98%, brigthness (L*) of 61.52. This WSP contained water, protein, ash, total sugar and pectin of 8.92%, 16.07%, 13.01%; 13.54%, and 57.24% respectively.